The relationship between anemia and sleep disturbances among older Chinese adults: The mediating role of handgrip strength - Jie Li; Zunyi Ma; Xiaojiang Zhao (PLoS ONE, 2025)
Background Sleep plays an important role in human health, and anemia can lead to a continuous deterioration of sleep. However, the association and mechanism between anemia and sleep disturbances remain unclear. This study aimed to examine the relationship between anemia and sleep disturbances among older Chinese adults, in addition to examining the mediating role of handgrip strength in this relationship. Methods This research utilized data from the 2015 China Health and Retirement Longitudinal Study (CHARLS). Following the application of specific inclusion and exclusion criteria, a total of 6,057 Chinese adults aged 60 and above were finally selected as the analysis samples. The dependent variable was sleep disturbances (yes/no), with anemia (present/absent) serving as the main independent variables. Handgrip strength was employed as the mediating factor. Multivariable-adjusted logistic regression analyses were conducted to investigate the relationships among anemia, handgrip strength, and sleep disturbances. Additionally, bootstrap tests were performed to assess the mediating role of handgrip strength in the association between anemia and sleep disturbances. Results In the unadjusted model, a positive association was observed between anemia and sleep disturbances (OR: 1.22, 95% CI: 1.08–1.38), whereas handgrip strength exhibited a negative association with sleep disturbances (OR: 0.95, 95% CI: 0.93–0.97). These associations persisted even after adjusting for covariates in Models 1, 2, and 3. Furthermore, handgrip strength was found to significantly mediate the link between anemia and sleep disturbances(mediating effect = 5.75x10 −3), with the mediating effect accounting for 15.67% of the association. Conclusions The study indicate that anemia is positively associated with an increased risk of sleep disturbances among older Chinese individuals, with handgrip strength acting as a significant mediator in this relationship. This study provides valuable references for improving the sleep quality of older adults.